Penerapan E-Commerce Dalam UMKM Kota Lhokseumawe - Rozatul Ikhwa; Rayyan Firdaus (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
With rapid developments in the fields of technology and information, people must start learning about the internet and staying connected to it. One of the things that is done is shopping online, or e-Commerce, which is a new lifestyle that is emerging at the moment. Large companies and UMKM utilize e-Commerce in the business world. As is the case in Lhokseumawe City, Banda Sakti District, Aceh Regency. The aim of this research is to apply e-Commerce to increase the competitiveness of UMKM.. Trade competition is normal. However, sellers, or manufacturers, have many ways to offer their goods or services. This can be via the internet, newspapers, magazines, etc. Therefore, an effective trading plan is needed for trading on this electronic platform. One of the UMKM in Lhokseumawe City which is the subject of this case study is to provide a complete picture of how e-Commerce is implemented in UMKM.